Fungsi Sosial Sekolah dalam Membentuk Individu dan Membangun Masyarakat - Ilham Hafizh Nurvalufi; Sigit Indartanto; Sekar Fitri Maharani (PT. AHLAL PUBLISHER NUSANTARA, 2026)
Schools are educational institutions that function not only as places for the transfer of knowledge but also as social institutions that play a significant role in shaping individuals and developing society. This study aims to analyze the social function of schools in shaping individuals’ ways of thinking, character formation, and their contribution to community development. The research employs a qualitative approach using a library research method by analyzing various relevant literature related to education and the social functions of schools. The findings indicate that schools play an essential role in developing scientific thinking, instilling social and moral values, and fostering individual potential to contribute to society. Furthermore, schools also function as centers for community empowerment through educational activities, literacy programs, and social capacity development. Therefore, optimizing the social function of schools is a crucial factor in improving individual quality and promoting sustainable societal development. Keywords: Social Function Of Schools, Education, Individual Development, Community Empowerment. Abstrak: Sekolah merupakan lembaga pendidikan yang tidak hanya berfungsi sebagai tempat transfer ilmu pengetahuan, tetapi juga memiliki peran sosial dalam membentuk individu dan mengembangkan masyarakat. Penelitian ini bertujuan untuk menganalisis fungsi sosial sekolah dalam membentuk pola pikir, karakter individu, serta kontribusinya terhadap pembangunan masyarakat. Metode penelitian yang digunakan adalah pendekatan kualitatif dengan jenis penelitian studi kepustakaan (library research) melalui analisis berbagai literatur yang relevan dengan kajian pendidikan dan fungsi sosial sekolah. Hasil penelitian menunjukkan bahwa sekolah memiliki peran penting dalam membentuk cara berpikir ilmiah, menanamkan nilai-nilai sosial dan moral, serta mengembangkan potensi individu agar mampu berkontribusi dalam kehidupan masyarakat. Selain itu, sekolah juga berfungsi sebagai pusat pemberdayaan masyarakat melalui kegiatan pendidikan, literasi, dan pengembangan kapasitas sosial. Dengan demikian, optimalisasi fungsi sosial sekolah menjadi salah satu faktor penting dalam meningkatkan kualitas individu sekaligus mendorong kemajuan masyarakat secara berkelanjutan. Kata Kunci: Fungsi Sosial Sekolah, Pendidikan, Pembentukan Individu, Pemberdayaan Masyarakat.